Draft Annual Plan 1986-87 Vol.-II Government of Tripura - Planning Commission (Planning Commission, 1986)
The economy of the State is mostly agrarian and more than 70% of population depends on agriculture. However, only about 25% of the total area is under cultivation. Paddy is the most important crop and constitutes over 72% of the total cropped area accounting for about 98% of total food grains production (about 3.73 lakhs M.T.) of the State during 1984-85. The average yield of rice in the state is 1402 Kg. per Hectare (1984-85) and compare favourably with the All India average of 1458 Kg./Hect. (1983-84).
Government of Tripura